Skin in the game: epidemiology analysis of skin cancer in rural Western Victoria - Tori Dopheide; Jessica Feeney; Joshua Eaton; Jessica Beattie; Rizwan Jaipurwala; Lara Fuller; Leesa Walker (Rural and Remote Health)
Introduction: The aim of this clinical review was to evaluate the number and types of skin cancer excised by GPs in a rural clinic in South West Victoria, Australia, and analyse the number needed to treat (NNT, a common metric for evaluating skin cancer detection) and the influence of clinician experience on diagnostic accuracy. Methods: This retrospective audit of patient records was for two discrete time periods (14 October 2019 to 5 November 2020 and 1 February 2021 to 17 February 2022). Data extracted included number of lesions removed, location of lesions, skin cancers detected, and patient and clinician characteristics. Results: A total of 789 lesions were excised; of these, 449 (56.9%) were histologically confirmed to be malignant. Males were statistically more likely to be diagnosed with a malignancy (p≤0.001). The NNTs for melanoma and non-melanoma skin cancers were 5.4 and 1.4, respectively. Experienced GPs (>5 years experience) were better at detecting melanoma and non-melanoma skin cancers than their junior colleagues. Conclusion: This study investigated the demographic characteristics of rural skin cancer patients and the diagnostic skills of GPs in South West Victoria. Results obtained found males had a higher risk of skin cancer than females. The diagnostic accuracy for all skin cancers improved with clinician experience and a lower overall NNT for both melanoma and non-melanoma skin cancers when compared to existing literature. Differences in this may highlight the experience, exposure, and professional interest of rural GPs, addressing a lack of specialist services in the area.